If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41x(x) + -12x + 48 = 4x(x)(x)(x) Multiply x * x 41x2 + -12x + 48 = 4x(x)(x)(x) Reorder the terms: 48 + -12x + 41x2 = 4x(x)(x)(x) Multiply x * x 48 + -12x + 41x2 = 4x2 * x * x Multiply x2 * x 48 + -12x + 41x2 = 4x3 * x Multiply x3 * x 48 + -12x + 41x2 = 4x4 Solving 48 + -12x + 41x2 = 4x4 Solving for variable 'x'. Combine like terms: 4x4 + -4x4 = 0 48 + -12x + 41x2 + -4x4 = 0 The solution to this equation could not be determined.
| (3x+1)=85 | | 8-8*2+3=0 | | 19x+.5ax=x+9 | | 3(3x+4)+97=11x+10-2x+99 | | 7x-y=43 | | 108+6x=180 | | 6(x+1)=6+7x | | 14p+15q+p-5q-7p= | | 5(c+3)=2(2c+11) | | 0.16(12)+0.04x=0.08(18+x) | | -2(6y-6)-y=-3(y-3) | | 4(x+6)-2(5-7x)= | | 11-5x=-7x+17 | | 4x-2y-12=0 | | 8x+6=abc | | -6=1-2n+5 | | (5n)*(5n)= | | 8-x=(x+6)(x+6) | | -b^5+2b^4-8= | | r+1.6=2r+1 | | 8428x-4116=98(86x-42) | | 7(9-3a)+13=13 | | 12x-6-8x=2x+2x-6 | | 30-6m-8=24 | | 180+0.15x=x-289.50 | | (5n)x(5n)= | | 4x+30=51 | | x(x+5)-2(x-4)=12 | | r+16=2r+1 | | 4x+6=x-2y | | 4x+x=51 | | X-2(2x-7)=2(x-8) |